MORE LIKES, MORE CLIMBING: AN INVESTIGATION OF CLIMBERS’ INTENTION TO USE SOCIAL MEDIA FOR SELF-PROMOTION - Arsova, Ilina; Adjanin, Nina (Sport - nauka i praksa, 2024)
Building on Ajzen’s (1991; 2013) Theory of Planned Behavior (TPB), this study aimed to investigate the predictors of social media use among climbers globally. It focused on factors such as attitude, subjective norm, and intention, examining their impact on climbers’ self-promotion across various social media platforms. The research encompassed activities spanning from natural environments to competitive sports climbing, emphasizing the evolving role of social media in these contexts. Employing a correlational research design, the study explored how TPB variables influence climbers’ engagement with social media for self-promotion within the climbing community. A sample of 142 climbers from 21 countries participated in an online survey, selected through purposeful and convenient sampling methods. All respondents confirmed their use of social media platforms for self-promotion, with Instagram emerging as the primary platform of choice. This research contributes to understanding the intersection of psychological factors and social media behavior among climbers, shedding light on how attitudes, social norms, and intentions shape online self-presentation in adventure sports. By examining these dynamics, the study provides insights into what drives climbers’ digital interactions and their implications for broader trends in sports communication and community engagement. Moreover, this study found that female climbers have a higher intention to use social media for self-promotion compared to male climbers.